AVAILABILITY OF TOURISM COMPONENTS IN LANTAN VILLAGE, CENTRAL LOMBOK DISTRICT, INDONESIA - Alievia, Alievia Putri Namira; Baiq Yatni Milana Putri; Arif Ismawan (Faculty of Economics and Business, University of Mataram, 2022)
Lantan is one of the villages located in North Batukliang District, Central Lombok Regency, West Nusa Tenggara Province, Indonesia. Lantan Village also borders several other villages, namely the north bordering the Protected Forest Area, the south with Aik Darek Village, the west with Karang Sidemen Village and Tanak Beak Village and the east bordering Aik Berik Village, Teraktak Village and Selebung Village. To make Lantan village a tourist village, an initial study is needed to determine its potential. This research is qualitative research, the data collection methods used are observation, interviews, documentation and literature study. Based on the results of the research that has been done The tourist attraction is Elong Tune Waterfall, besides being able to enjoy Elong Tune waterfall, tourists can also enjoy other supporting facilities at that location including taking pictures, relaxing in the barracks and playing swings. In addition, access to the location is feasible and in good condition. Other facilities in the Lantan tourism village are public toilets and barugak. Finally, ancillary services where in the Lantan tourist village there is a Pokdarwis as the manager of the Lantan tourist village.